Everything That Will Be Written Has Already Been Told: Sources of the Notion of a Retrospective Future in Constrained Writing in Hebrew Literature - Hagbi, Yaniv (MiKAN, 2022)
The conscious use of literary constraints has become a widespread phenomenon in Modem Hebrew literature. The choice to use a formal apparatus for a given work of art before its concrete formation can involve the use of traditional constraints (such as the sonnet) or the creation of completely new ones. The artistic constraint and its use are at the heart of literary group Oulipo’s activity. The introduction of Oulipo and its members into the discourse of Hebrew literature is not the only reason for the rise of pre- constrained writing in Hebrew literature in recent decades. However quite remarkably, various key ideas in the group’s work share a great affinity with rabbinical ideas, mainly in regard to the conception of language and interpretation. This article is dedicated to one of these notions. The central Oulipian idea, which is formulating a constraint by which new works can be produced and created, is very similar to the idea of constant interpretation in rabbinic literature. Moreover, new works that are made possible by the constraint simultaneously reside in the future, as a potential, and in the past, as a realization within the constraint itself before it has been actualized. This is an inherent, non-linear conception of time, or in the language of the Talmud: “Anything an accomplished student innovates in the future has already been told to Moses on Mt. Sinai.” That same “future,” in which everything “has already been told” is the subject of this article. Here, too, lies the same tension between the determinism dictated by language and its own constraints, and the freedom of its users to create within it - the tension between being “etched” (Haruf) and the experience of “freedom”” (Heruf). This article demonstrates how the blurring of linear time is an essential part of both Oulipian and Rabbinical thought. It does so by describing the connection between Diodorus Cronos’ (3407-284 BC) famous “Master Argument,” the Oulipian notion of constraint, and the idea of the dual Torah given on Mount Sinai: the written and the oral. The linear time of past-present-future we are accustomed to is replaced by a past that takes place in the future and crated in the present.